THE EFFECT OF GUIDED INQUIRY MODEL ON HIGHER ORDER THINKING SKILLS REVIEWED FROM CHEMICAL LITERACY - Rendy Priyasmika; Ika Farida Yuliana (JCER (Journal of Chemistry Education Research), 2021)
Abstract. The change in the educational paradigm in the 21st century requires students to have good basic knowledge and understanding to develop Higher Order Thinking Skills (HOTS). Chemical equilibrium is an abstract material and complex, so it requires good thinking skills to understand the concepts. This Study aims to determine the effect of the application of guided inquiry models on HOTS in chemical equilibrium. This research uses Pre-Experimental Design with One Shot Case Study model with 25 students of Billfath University as subjects. The data were collected using the HOTS test instrument in the form of 15 multiple choice questions. Hypothesis testing used the Independent Sample T-test (non-parametric). The results showed (1) the high-level learning outcomes of students with high initial abilities were better than students with low initial abilities, (2) there was a significant effect of applying the model Guided inquiry learning towards student high-level learning outcomes.